Penyediaan Alat Pencuci Tangan (Wastafel) Otomatis Untuk Pencegahan Penyebaran Covid 19 Di Rumah Sakit Chasan Bosoeri Ternate - Iis Hamsir Ayub Wahab; Muhammad Yunus H Abbas; Bambang Tjiroso (Universitas Khairun, 2021)
Washing hands is a simple thing, but has a very important role in everyday life. The sink system is designed to meet these needs. The sink system consists of a water faucet, and soap. The sink system has begun to be widely used in homes, schools, campuses, offices, industry and other places. This service aims to design and make automatic hand washing wasaffles so that it is hoped that it can make hand washing activities easier and more practical. Users no longer need to turn the water tap and pick up soap, just by placing their hands in a certain position, the water and liquid soap will come out automatically. The results of the implementation of the activities are the process of assembly, installation and delivery. The PKM team also conducted socialization on the use of tools to users, namely the Chasan Bosoeri Ternate Hospital. Reporting and publication is carried out after each stage has been completed. The published articles are published in the LPPM journal, Khairun University.